2020
DOI: 10.3390/ma14010151
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Light Treatment of Titanium Enhances Attachment, Adhesion, and Retention of Human Oral Epithelial Cells via Decarbonization

Abstract: Early establishment of soft-tissue adhesion and seal at the transmucosal and transcutaneous surface of implants is crucial to prevent infection and ensure the long-term stability and function of implants. Herein, we tested the hypothesis that treatment of titanium with ultraviolet (UV) light would enhance its interaction with epithelial cells. X-ray spectroscopy showed that UV treatment significantly reduced the atomic percentage of surface carbon on titanium from 46.1% to 28.6%. Peak fitting analysis revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 49 publications
2
27
0
Order By: Relevance
“…UV-treated titanium can collect or attract host-derived proteins on its surface, which results in enhanced bioactivity for both osteoblasts and fibroblasts. In addition, the attachment of gingival epithelial cells is enhanced on UV-treated titanium surfaces [124]. Taken together with the present study, soft tissue sealing could be enhanced by UV treatment.…”
Section: Discussionsupporting
confidence: 83%
“…UV-treated titanium can collect or attract host-derived proteins on its surface, which results in enhanced bioactivity for both osteoblasts and fibroblasts. In addition, the attachment of gingival epithelial cells is enhanced on UV-treated titanium surfaces [124]. Taken together with the present study, soft tissue sealing could be enhanced by UV treatment.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies have reported that neutrophils, T cells, and leukocytes are implicated in the in ammatory response and immune escape process of periodontitis [36,37]. Attachment, adhesion and retention of primary human gingival broblasts and microvascular formation are the main healing processes of periodontitis against microbial damage [38][39][40][41]. The level of serum IgG and salivary crossreactive IgG in patients with periodontitis is signi cantly high and is correlated with the severity of periodontitis [42].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, both null hypotheses were rejected. The UV photofunctionalization might help replace the HF as a decontaminant agent, as demonstrated in implant and miniscrew surfaces [ 16 , 22 , 33 ]. Furthermore, due to the indirect restorations' occlusal adjustment and saliva contamination during try-in [ 34 , 35 ], it is expected that dentists would return the restorations to the dental laboratory for repolishing of outer surfaces [ 36 ] and sandblasting of inner surfaces [ 34 36 ].…”
Section: Discussionmentioning
confidence: 99%